International Patent Law Conflicts With the Right of Access to Medicines and Healthcare: Key Aspects - Simonyan, Ani (Bulletin of Yerevan University C: Jurisprudence, 2023)
This article is dedicated to the legal conflicts between international patent law and the right of access to medicines and healthcare. This article discusses the problem above under the light of the framework of the international agreements, mainly WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) and Doha Declaration on the TRIPS agreement and public health. As we know, patents give exclusive rights to the inventors to use their innovations for a long period of time. This limits the ability of public to get easy access to medications, consequently to indispensable healthcare. It is undoubtable that the quality of life and the healthcare of the public is an absolute priority. On the contrary, the expropriation of patent rights, inadequate compensation of damages for issuing the compulsory licensing may have irreversible consequences for the states. Foreign investor may file claims against the governmental authorities to ad hoc or permanent arbitral institutions.